Unruly cinema : history, politics, and Bollywood - Mehta, Rini Bhattacharya (University of Illinois Press, 2020)
"Between 1931 and 2000, India's popular cinema steadily overcame Hollywood domination. Bollywood, the film industry centered in Mumbai, became nothing less than a global cultural juggernaut. But Bollywood is merely one part of the country's prolific, multilingual cinema. Unruly Cinema looks at the complex series of events that allowed the entire Indian film industry to defy attempts to control, reform, and refine it in the twentieth century and beyond. Rini Bhattacharya Mehta considers four aspects of Indian cinema's complicated history. She begins with the industry's surprising, market-driven triumph over imports from Hollywood and elsewhere in the 1930s. From there she explores how the nationalist social melodrama outwitted the government with its 1950s cinematic lyrical manifestoes. In the 1970s, an action cinema centered on the angry young male co-opted the voice of the oppressed. Finally, Mehta examines Indian film's discovery of the global neoliberal aesthetic that encouraged the emergence of Bollywood"--